Olive oil and the millennial generation in Chile. What do these consumers consider when buying this product? - Mora, Marcos; Schnettler, Berta; Lobos, Germán; Geldes, Cristian; Boza, Sofía; Lapo, María del Carmen; Paz, Ruth (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
This study aimed to identify the attributes influencing the purchase decision process of the olive oil consumer belonging to "Millennials" in the Metropolitan Region, Chile. The method includes data collection from 408 people and a combination of factorial and cluster analysis. The results identified two segments in the millennial consumers. In the purchasing, one of the consumer groups, with 150 people, attached importance to product information and origin, as well as oil category, colour, and acidity. The other group with 258 people rejected a large part of the attributes, except for that related to electronic commerce. These results suggest that the search for attractive attributes in a broad sense is relevant and should be considered in the development of commercial strategies for the segment that positively values all attributes. However, for that segment rejecting intrinsic attributes, it would be advisable to deepen on aspects related to technology and social network. Highlights Young consumers of olive oil in Chile. Signs for product development and marketing channels in the millennial generation. Important receptivity of the electronic channel for the marketing of olive oil.